Evaluation of a pediatric navigation program within primary care: a quantitative analysis guided by the Reach, Effectiveness, Adoption, Implementation, Maintenance (RE-AIM) framework - Mackenzie Stuenkel; Caitlin Koob; Sarah F. Griffin; Kerry K. Sease (BMC Health Services Research, 2024)
Abstract Background Pediatric Support Services (PSS) is a Patient Navigation Program designed to address barriers from referral-to-service connection from primary care to health system and community-based services and resources. This study aimed to evaluate PSS’ implementation for mental health services along the Reach, Effectiveness, Adoption, Implementation, Maintenance (RE-AIM) framework and identify factors throughout implementation to inform sustainability and delivery. Methods This study included descriptive analysis of all patients referred to PSS to assess reach, with a primary cohort analyses of a subset of patients referred specifically to mental health services. Data collection included triangulation of information extracted from electronic health records, direct contact with patients’ caregivers, and follow-up surveys completed by patients’ caregivers. Analyses were designed within each construct of the RE-AIM framework, and assessed for their tiered impact on the patient, provider, and system levels. Results From October 2019 to June 2023, 13,109 total referrals for 11,214 unique patients were triaged by PSS. The patient population overrepresented younger, Hispanic, female patients compared to the clinical population included in this health system’s service area. Of these patients, 3,929 were followed-up by trained navigators at two-weeks for mental health service connection, with 50.6% reported being connected to referred services and an additional 27.1% with pending appointments. There was a significant increase in referral connection rate as age increased and for Black patients, compared to other children. For patients considered connected to or pending services, a satisfaction survey found high satisfaction with PSS and the amount of navigator-patient contact (81.5 and 79.6%, respectively). Conclusion These findings highlight potential program modifications to optimize quality of care and health for children and families, while enhancing capacity among providers, navigators, and clinics. Further adaptations, including electronic health record integration, patient/family feedback, and automated navigation processes, are suggested next steps for comprehensive navigation. Trial registration This study was approved by the Institutional Review Board for Prisma Health, trial number 1,852,794, with the most recent approval for expanded evaluation received on June 15, 2022 (original application approved in 2016).